Use of antegrade dissection re-entry in coronary chronic total occlusion percutaneous coronary intervention in a contemporary multicenter registry. (1st July 2016) - Danek, Barbara Anna; Karatasakis, Aris; Karmpaliotis, Dimitri; Alaswad, Khaldoon; Yeh, Robert W.; Jaffer, Farouc A.; Patel, Mitul; Bahadorani, John; Lombardi, William L.; Wyman, Michael R.; Grantham, J. Aaron; Doing, Anthony; et al.
Abstract: Background: We assessed efficacy and safety of chronic total occlusion (CTO) percutaneous coronary intervention (PCI) using antegrade dissection re-entry (ADR). Methods: We examined outcomes of ADR among 1313 CTO PCIs performed at 11 US centers between 2012–2015. Results: 84.1% of patients were men. Prevalence of prior coronary artery bypass graft surgery was 34.3%. Overall technical and procedural success were 90.1% and 88.7%, respectively. In-hospital major adverse cardiovascular events (MACE) occurred in 31 patients (2.4%). ADR was used in 458 cases (34.9%), and was the first strategy in 169 cases (12.9%). ADR cases were angiographically more complex than non-ADR cases (mean J-CTO score: 2.8 ± 1.2 vs. 2.4 ± 1.2, p < 0.001). ADR was performed using the CrossBoss catheter in 246 of 458 (53.7%) and the Stingray system in 251 ADR cases (54.8%). Compared with non-ADR cases, ADR cases had lower technical (86.9% vs. 91.8%, p = 0.005) and procedural success (85.0% vs. 90.7%, p = 0.002), but similar risk for MACE (2.9% vs. 2.2%, p = 0.42). ADR was associated with longer procedure and fluoroscopy time, and higher patient air kerma dose and contrast volume (all p < 0.001). After excluding retrograde cases, ADR and antegrade wire escalation (AWE) had similar technical success (92.7% vs. 94.2%, p = 0.43), procedural success (91.8% vs. 94.1%, p = 0.23), and MACE (2.1% vs. 0.6%, p = 0.12). Conclusions: ADR is used relatively frequently in contemporary CTO PCI, especially for challenging lesions and after failure of other strategies. ADR is associated with similar success rates and risk for complications as compared with AWE, and is important for achieving high procedural success.